An insider’s guide to the street dance subculture in Singapore. - Wong, Elke Pao Yi. (2011)
This paper examines the vibrant subculture of street dance (dance styles that have evolved outside the studio) in Singapore. It conceptualises the social space of street dance, through processes of construction, consumption and contestation. This paper pays homage to the social order that dancers respect; an order they have established and continued to shape. It examines the methods dancers use to establish territories within physical and aural space. It also traces the flows between the local-global street dance landscape; a platform where channels of ideology, knowledge and talent are created and produced. Most of the research is situated at *SCAPE, a spanking-new shopping mall in Singapore, and the latest home to local street dance subculture.